LEXICAL BORORWINGS IN ERGONOMICS BASED ON ELECTRONIC MEDIA IN UZBEK (International journal of artificial intelligence, 2025)
This article explores how foreign borrowings, especially English terms, are used in naming online media and services. It focuses on how internet ergonyms - names of online shops, platforms, and media pages - reflect globalization and modern branding. the lexical borrowings in the field of ergonomics based on electronic media in the Uzbek language are analyzed. Special attention is paid to foreign-origin terms such as magic safari, magic mama, supermarket, minimarket, office, official, and others that have entered the Uzbek lexicon through advertisements, digital platforms, and everyday usage. The study explores the semantic adaptation, phonetic assimilation, and functional roles of these borrowed words in the modern Uzbek linguistic landscape. The influence of globalization and media on the enrichment and transformation of the Uzbek vocabulary is also examined. The research highlights how these borrowings reflect socio - cultural trends and affect language norms, especially in commercial and technological domains.